PENGARUH PENDIDIKAN KARAKTER TERHADAP PRESTASI BELAJAR SISWA KELAS TINGGI SD NEGERI 006 RAMBAH SAMO - Rinja Efendi; Asih Ria Ningsih; Pariang Sonang Siregar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Character building should be something that must be done continuously without stopping either through coaching, habituation, coaching and other things that improve the character improvement of students. The characters that have been formed will show student behavior through attitudes. Based on observations made at SD Negeri 002 Rambah Samo for the 2019/2020 school year, character education has been implemented through several indicators of character education, so that it will have an impact on student achievement. This study aims to reveal whether there is an effect of character education on student achievement in SD Negeri 006, Rambah Samo District. The hypothesis proposed in this study is character education has an effect on learning achievement. This type of research is simple linear correlation and regression. The research method used in this research is correlational quantitative method. The population in this study were high-grade students (Class IV, V and VI) SD Negeri 006 Rambah Samo, Rokan Hulu Regency, totaling 107 students. The sample size was determined using the Slovin formula, so that the total sample size was 84 students. Data were collected using a Likert scale model questionnaire which has been tested for validity and reliability. Test the questionnaire by comparingvalue Cronbach's alpha (0.620).   The results obtained in testing the research instrument were 0.848, greater than 0.620, so the research instrument was said to be reliable or valid. The results of data analysis showed that the effect of character education on learning achievement was obtained by 52.3%. The level of achievement of the character education variable is in the quite good category, namely 79.25%. Meanwhile, the level of the respondents' achievement in the learning achievement variable was obtained by 77.26% with a fairly good category.